Study on the Static Stiffness of the Flexible Composite Connecting Rod - Zong Hao; Yin Xunmin; Ding Chunhua; Sheng Guibin; Xing Lifeng (Jixie chuandong)
The axial and radial stiffness formula of the flexible composite connecting rod is obtained by the theory analysis. The mechanical property constant of rubber Mooney- Rivlin model is determined by uniaxial tensile experiment,the static stiffness analysis of the flexible composite connecting rod are carried out by using ABAQUS. The experimental results prove the validity of the theoretical calculation and finite element simulation calculation. The experiment result shows that the research method is accurate and effective. The research results have certain guiding significance for design of the flexible composite connecting rod.